2006
DOI: 10.1007/s11434-006-1269-z
|View full text |Cite
|
Sign up to set email alerts
|

Pulse width effect on the dissociation probability of CH4 + in the intense femtosecond laser field

Abstract: The laser pulse width effect on the dissociation probability of CH 4 + irradiated by an ultrafast laser has been investigated experimentally and theoretically. The femtosecond laser at 800 nm with an intensity of 8.0 × 10 13 W/cm 2 was used. The observed relative yield of the primary fragment ion CH 3 + increases with increasing pulse width and tends to saturate when the pulse width is longer than 120 fs. The field-assisted dissociation (FAD) model and quasi-classical trajectory (QCT) calculation were applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Within the laserpulse temporal duration and spatial distribution, the potential surfaces can be modified by the laser electric field, and if the laser intensity is strong enough, it can induce the ion dissociation during the laser duration. This type of dissociation is usually referred to as FAD [19][20][21] and occurs in the femtosecond range. The second type of ion dissociation occurs outside the temporal and spatial influence of the femtosecond laser pulse.…”
Section: Theoretical Treatments Of Dissociation Of Molecular Ionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the laserpulse temporal duration and spatial distribution, the potential surfaces can be modified by the laser electric field, and if the laser intensity is strong enough, it can induce the ion dissociation during the laser duration. This type of dissociation is usually referred to as FAD [19][20][21] and occurs in the femtosecond range. The second type of ion dissociation occurs outside the temporal and spatial influence of the femtosecond laser pulse.…”
Section: Theoretical Treatments Of Dissociation Of Molecular Ionsmentioning
confidence: 99%
“…For the case in which the laser duration was 8 fs, only the primarily fragmental CH 3 + ion was observed, in addition to the parent CH 4 + ion. When the laser duration was increased to 30 fs, CH 2 + and H + began to appear, and when the laser duration reached 110 fs, some doubly charged ions were also observed, in addition to the abundant singly charged ions. , The field-assisted dissociation (FAD) model and quasi-classical trajectory (QCD) calculation were applied to predict the dissociation probability of CH 4 + . The calculated probability was corrected with the molecular orientation effect and the spatial distribution of laser intensity. The modified results indicated that the dissociation would require at least 23 fs and was saturated with long pulse widths (∼100 fs).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Wu et al 24 practically studied the fragmentation pattern of CH 4 due to femtosecond laser shots. Wang et al 25 investigated the methane dissociation using femtosecond laser shots at 800 nm using the laser fluence ∼10 14 W/cm 2 . Suzuki et al 26 demonstrated the formation of formaldehyde from photo-oxidation of methane over a molybdena-silica catalyst at ∼500 K using UV irradiation.…”
Section: Introductionmentioning
confidence: 99%